Asociación de polimorfismos de nucleótido simple y de haplotipos para el gen de la Leptina con la ganancia de peso en la raza bovina blanco orejinegro usando técnicas bayesianas (2012)
This paper presents a Bayesian methodology for association study of single nucleotide polymorphism (SNP) and haplotypes with a special interest in animal production. In the ﬁrst stage, we propose a Bayesian linear model to select the SNPs that have an eﬀect on the average of the genetic value in the response variable. In a second stage, after the identiﬁcation of haplotypes compatible with genotypes of inﬂuence in the ﬁrst stage, we discuss the application of a general linear model and a logistic regression model in order to identify those haplotypes having a higher association with the increasing of genetic values. In both stages, Bayesian methodologies are used when appropriate and Monte Carlo simulation methods are implemented in order to generate Markov Chains whose stationary distribution corresponds to the conditional posterior distribution of the parameters of interest. The practical application is subject to animal production in a Colombian bovine breed.